1994
DOI: 10.1021/cm00048a018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant/Silica Molar Ratios on the Formation of Mesoporous Molecular Sieves: Inorganic Mimicry of Surfactant Liquid-Crystal Phases and Mechanistic Implications

Abstract: The influence of surfactanthilica molar ratio (Sur/Si) in the synthesis of the mesoporous molecular sieve materials (M41S) was studied in a simple ternary synthesis system containing tetraethylorthosilicate (TEOS), water, and the cetyltrimethylammonium (CTMA) cation at 100 "C. The resulting silicate materials were characterized by X-ray diffraction, 29Si NMR, and FTIR. As the Sur/Si molar ratio increased from 0.5 to 2, the siliceous products obtained could be classified into four separate groups: MCM-41 (hexag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
270
1
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(296 citation statements)
references
References 5 publications
16
270
1
9
Order By: Relevance
“…The 2D hexagonal p6m (MCM-41), the 3D cubic Ia3d (MCM-48) and the lamellar p2 (MCM-50) are the common mesophases in silicas with pore sizes between 2 and 5 nm [31]. Similarly, 2D hexagonal p6m is reported in MSNs with large pore size 6-20 nm [33].…”
Section: Lin Et Al Obtained Different Antibacterial Effects In Ionicmentioning
confidence: 95%
“…The 2D hexagonal p6m (MCM-41), the 3D cubic Ia3d (MCM-48) and the lamellar p2 (MCM-50) are the common mesophases in silicas with pore sizes between 2 and 5 nm [31]. Similarly, 2D hexagonal p6m is reported in MSNs with large pore size 6-20 nm [33].…”
Section: Lin Et Al Obtained Different Antibacterial Effects In Ionicmentioning
confidence: 95%
“…The general pattern for the formation of mesoporous silicates is shown in and their hydrophilic head groups orientating outside to provide protection from water molecules. In order to form the micelles, the critical micelle concentration at a set temperature must be exceeded 54 . These organized micellar liquid crystal structures act as templates so that the inorganic substances can attach around them.…”
Section: Mesoporous Silicatesmentioning
confidence: 99%
“…It was reported that the surfactant to silica ratio was the crucial parameter in determining the shape of the micelle aggregates. [35] More recently, n-alkanes of different chain lengths were used as swelling agents for the mesoporous products. [36] The pore diameters of the products increased proportionally with the length of the n-alkanes, containing up to 15 carbon atoms.…”
Section: Synthetic Aspects: Template Theory For Mesoporous Oxides Synmentioning
confidence: 99%